A Study on Information Need among Rural Masses in Nagra Block of Ballia District (U.P.) (Indian Journal of Extension Education, 2013)
The study was conducted in the Community Development Block, Nagra in the Ballia district of Uttar Pradesh. Ballia district is the eastern most part of the Uttar Pradesh state and borders of Bihar state. There are 160 villages in the Nagra Block of Ballia district. Four villages namely Nagra, Tadi Badagaon, Nikashi and Kasaundar were randomly selected. Fifty respondents were selected from each of the selected villages through random sampling technique. Thus, a total of 200 respondents were selected for the purpose of study. The study with an objective to assess the relationship of demographic characteristics with information need, availability and utilization pattern of information sources among rural masses. An Ex-Post Facto research design was used for the present study. Different variables selected were average age of the family, educational status of the family, caste category, socio-economic status, income, land holding, material possession, size of family and type of family. Data were collected through interview schedule, observation and informal interpersonal discussion with the villagers.The data revealed that majority of the respondents were of middle age, having medium level of education and middle socio-economic status. Maximum number of respondents were from general caste category having large family size. Maximum number of respondents were small farmers belonging to middle income group and had medium level of material possession. Majority of farm families had medium level of information needs in which agriculture was found to be the top priority area. It was found that information need and availability of information source to respondents was positively and significantly related with demographic variables like educational status of the family, caste category, socioeconomic status, income, land holding, material possession, size of family and type of family at one per cent level of significance. The study indicated that mass media sources were most utilized by higher socio-economic status group.